2008
DOI: 10.1063/1.2968244
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanocluster crystallization in SiOx films studied by Raman scattering

Abstract: Precipitation and crystallization of Si nanocrystals have been monitored by means of Raman spectroscopy. SiOx films with different compositions have been deposited by low-pressure chemical-vapor deposition technique onto silica substrates and treated to temperatures exceeding 800 °C. The evolution of the Raman signal with the thermal budget reveals that the silicon transition from amorphous to crystalline state shifts to higher temperatures as the Si content in the layers is lowered. A rather complete crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 24 publications
14
74
1
1
Order By: Relevance
“…As we mentioned above, this discrepancy is explained in terms of the amorphous Si-shell that surrounds the crystalline core. 14,15 We found that the thickness of the amorphous shell gets larger as the stoichiometry approaches the one of pure SiO 2 , while the total cluster size is almost constant in all the explored range. The crystalline fraction (i.e., relative volume ratio between the crystalline and amorphous silicon regions) has been estimated by considering the size distribution of the whole clusters and the crystalline parts, obtained from the images of both TEM configurations.…”
Section: -2mentioning
confidence: 76%
See 1 more Smart Citation
“…As we mentioned above, this discrepancy is explained in terms of the amorphous Si-shell that surrounds the crystalline core. 14,15 We found that the thickness of the amorphous shell gets larger as the stoichiometry approaches the one of pure SiO 2 , while the total cluster size is almost constant in all the explored range. The crystalline fraction (i.e., relative volume ratio between the crystalline and amorphous silicon regions) has been estimated by considering the size distribution of the whole clusters and the crystalline parts, obtained from the images of both TEM configurations.…”
Section: -2mentioning
confidence: 76%
“…Consequently, size distribution of the whole cluster and their areal density can be extracted from EFTEM images, while the size distribution of the crystalline precipitates is obtained by means of HRTEM imaging (only the precipitates oriented along a high symmetry crystalline direction are observed using this configuration). Assuming that the Si-nanoaggregates have a spherical shape and are formed by a crystalline core surrounded by an amorphous shell (coreshell model 14,15 ), EFTEM and HRTEM configurations are complementary, providing information either from the whole clusters or only on their crystalline core, respectively. We found that the diameter of the Si-aggregates obtained by both configurations nicely follow a log-normal distribution, f(d clu,cry , r clu,cry ) where d clu,cry , d 0 clu,cry , and r clu,cry are the diameter, mean diameter, and broadening of the size distribution, respectively, for either whole clusters (clu) or crystalline cores (cry).…”
Section: -2mentioning
confidence: 99%
“…This compaction has also been reported in reference [17]. The hydrogen comes from the decomposition of silane (SiH 4 ) gas precursor, so the densification of the layers is more evident in samples with high Si contents.…”
Section: Structural Characterizationmentioning
confidence: 80%
“…Silicon nanocrystals are frequently characterized by means of Raman spectroscopy that provides very detailed information on their crystal structure [8][9][10][11]. For bulk Si, triply degenerate (T 2g ) first-order optical phonon at the Brillouin-zone centre is observed at 521 cm -1 .…”
Section: Introductionmentioning
confidence: 99%